Class Management in Improving Achievement Student Learning - Clara Tri Putri; Putri Febby Aulia; Yunita Aisyah; Sari Bulan Hasibuan (Edumaspul: Jurnal Pendidikan, 2022)
The results of scientific research show that teachers' teaching strategies use learning strategies that have various models, including learning strategies using individual approaches and group learning methods so that teachers and students are easier and improve the quality of learning that is mastered by a teacher. The teacher's teaching strategy has a very important role in improving student learning achievement in an effort to produce quality students who are knowledgeable, intelligent, insightful, have noble character and are able to improve student learning achievement